Šimáně 2020: Student Conference on Nuclear Engineering - Editorial, Foreword (Acta Polytechnica CTU Proceedings, 2020)
Nuclear-related sciences and technology have a long and rich history within the Czechoslovakia. Even though the Czech Republic and Slovakia have been separated since 1993, wide cooperation on different levels including education and research still exists. In order to support cooperation and good relations between Czech and Slovak students in nuclear engineering and related disciplines, the Department of Nuclear Reactors organizes annually a student conference on nuclear engineering - Šimáně. Students mainly from Czech and Slovakian nuclear institutes are invited to present their research and share their knowledge. Participants from other foreign institutes are welcomed as well.